Finanzierungsstrukturen im Vergleich - Ramb, Fred (ZEW, 1998)
Thirty years after the seminal work of Modigliani and Miller and countless articles the capital structure puzzle is for the most part unsolved. Especially, in this field of research there is a considerable lack of empirical evidence. Using firm level data from seven European countries, this paper tries to analyze differences in the determinants of capital structure due to legal forms. For the most countries, including Germany, France, Spain, and the Netherland, legal form exerts only a slight impact on the determinants of capital structure. In contrast, only in the UK, and Italy there are considerable effects of legal form on financing patterns. Taken together, earlier empirical evidence for stock market firms seems to hold for other legal forms.
Literaturverz. S. 39 - 41
Keywords: Arbeitspapier; Graue Literatur; Buch; Kapitalstruktur; Rechtsform; Prinzipal-Agent-Theorie; Asymmetrische Information; Finanzsystem; Schätzung; Europa